FINANCIAL STRATEGY IN THE FINANCIAL MANAGEMENT SYSTEM OF ENTERPRISE - NIKOLCHUK, Yuliia; LOPATOVSKA, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article investigates the theoretical issues of forming the financial strategy of the enterprise in modern conditions of economic development. Different approaches to the definition of the concept of "financial strategy of the enterprise" are considered, the author's approach to its interpretation is offered. The essence of the financial strategy is to determine the priority goals and system of measures to achieve them in the field of financial resources, optimization of capital structure and efficiency of assets that meet the general concept of enterprise development and ensure its implementation; it is based on the analysis of financial condition, analysis of economic performance, efficiency and quality of enterprise management, forecasts and analysis of the dynamics of markets for products, assessment of potential risks (credit, investment, and currency, etc.), as well as analysis strengths and weaknesses of the enterprise, its competitive positions. The characteristic features of the financial strategy of the enterprise are reflected. It is noted that the financial strategy is consistent with the overall strategy of the enterprise and is a factor in ensuring its effective functioning and financial development in the future. The overall strategy is based on taking into account the possibilities of increasing the competitive advantages of the enterprise. The financial strategy is aimed at ensuring self-financing of the enterprise, which can be achieved in the context of effective management of capital, assets, profits, investments and more. Thus, the formation of strategic goals is focused on the accumulation of capital of the enterprise, sufficient to finance its expanded reproductionThe main stages of the process of development and formation of the financial strategy of the enterprise are substantiated. It is proved that the financial strategy is the guiding vector of enterprise management and its production and economic activity in the modern globalized, dynamic and competitive market environment. Prospects for further research are to justify the mechanism of formation and implementation of the financial strategy of the enterprise taking into account the situation and trends development of financial markets, as well as risk factors due to various transformation processes taking place in Ukraine today.
Keywords: enterprise strategy; financial resources; financial strategy; strategic management; enterprise management system